Evidence Limitations on the Part of the Entrepreneur in the Economic Process - Rzewuski, Maciej (Review of European and Comparative Law, 2023)
This article addresses an issue that is highly debatable both in the theory of civil procedural law and in the practice of jurisprudence, namely the entrepreneur’s right to a court and, consequently, the possibility of respecting the principle of material truth in a separate proceeding in commercial cases in the context of evidentiary limitations introduced by the legislator under the Act of 4 July 2019 amending the Code of Civil Procedure. Due to the fact that eponymous matters are complex and multifaceted, the present article shall describe and signal selected specific issues, which seem to raise the most doubts among representatives of the world of science and practitioners who apply civil law daily.